Design and Strategy for Welfare-to-Work Policy Implementation in Indonesia: Study on Multiple Activation, Strategy for Strengthening Service Provider Capacity and Response of Affected Groups of Pre-Employment Card (Kartu Prakerja) Program - Muhyiddin Muhyiddin; Rita Parmawati; Muhammad Qomaruddin; Fadillah Putra; Anwar Sanusi (Ministry of National Development Planning Republic of Indonesia/Bappenas, 2022)
The Covid-19 Pandemic has hit several countries in the world, including Indonesia. Some of those affected were the industrial world, which resulted in layoffs. In principle, the Pre-Employment Card is a bridge that connects the community with various kinds of new skills training. In addition, the Government also hopes to create a more capable and empowered society to simultaneously reduce excessive dependence on others. This research uses a mixed-method approach and explores the implementation process of the Pre-Employment Card program. The conclusion of this study directs that the pre-employment card program is a policy issued by the Government in the midst of the Covid-19 Pandemic as a social safety net and to train and improve the competence of the workforce to face the demographic bonus in 2030. Socialization carried out by the agency is only through the media social Instagram. In addition, the interaction that occurs in the account is very minimal, so the socialization carried out on social media can be said to be very minimal and less effective.